PENGGUNAAN CANVA SEBAGAI MEDIA INTERAKTIF DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PADA PEMBELAJARAN PENDIDIKAN PANCASILA UNTUK SISWA SD KELAS IV - Erdyati, Firda; Meliasari, Wa Ode; Damayanti, Maryam Isnaini; Sulistriyaniva, Ratna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aim of this study is to create and evaluate how Canva, as an interactive media, can help elementary school students (SD) improve their critical thinking skills while learning about Pancasila Education. Canva is a user-friendly graphic design platform designed to present innovative and engaging educational content. The Research and Development (R&D) approach uses the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Fourth-grade elementary school students in Sidoarjo were the subjects of this research. During the analysis stage, assessments and surveys of teachers and students identified the need for interactive learning media. The design process included creating a prototype of teaching materials using Canva. The development stage consisted of several trials and revisions made by users. Implementation was carried out by integrating Canva-based materials into different learning sessions. Critical thinking skills tests and observations of student behavior during learning were part of the final evaluation.The research results showed that the use of Canva significantly improved students' critical thinking skills, as indicated by better test scores for analysis, synthesis, and evaluation. Students were more active and motivated during the learning process, according to observations. Teachers reported that Canva helped make abstract concepts of Pancasila easier to understand and more engaging. The conclusion of this study suggests that elementary school students can enhance their critical thinking skills by using Canva-based learning media. Further research is needed to test other interactive media applications and to evaluate the long-term impact of using Canva in education.